2020
DOI: 10.1097/qai.0000000000002236
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of HIV-Infected Women Receiving Antiretroviral Therapy After Transferring Out of an Integrated Maternal and Child Health Service in South Africa

Abstract: Background: Integrated maternal and child health (MCH) services improve women's postpartum antiretroviral therapy (ART) outcomes during breastfeeding; however, long-term outcomes after transfer to general ART services remain unknown. Methods: The MCH-ART trial demonstrated that maternal retention and viral suppression at 12-months postpartum were improved significantly among women randomized to integrated MCH services continued in the antenatal clinic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
2
20
1
Order By: Relevance
“…We additionally report that approximately 80% retained in this cohort had durable VLS to 24 months, which will confer increased benefit in preventing HIV transmission during breastfeeding and subsequent pregnancies, as well as preservation of health in mothers. However, the proportion of women achieving durable VLS in our study is higher than that reported in South Africa (70% (<50 copies/mL) at 12 months and 56% at 36-60 months (median 44 months post-partum)) [18] and in Kenya (67% (<1000 copies/mL) at 12months) [19]. These differences may be explained by diverse proportions of retention and loss to follow-up across these different settings, including that women retained to 24 months in our study may not reflect population-level VLS among all post-partum Malawian women.…”
Section: Plos Onecontrasting
confidence: 90%
“…We additionally report that approximately 80% retained in this cohort had durable VLS to 24 months, which will confer increased benefit in preventing HIV transmission during breastfeeding and subsequent pregnancies, as well as preservation of health in mothers. However, the proportion of women achieving durable VLS in our study is higher than that reported in South Africa (70% (<50 copies/mL) at 12 months and 56% at 36-60 months (median 44 months post-partum)) [18] and in Kenya (67% (<1000 copies/mL) at 12months) [19]. These differences may be explained by diverse proportions of retention and loss to follow-up across these different settings, including that women retained to 24 months in our study may not reflect population-level VLS among all post-partum Malawian women.…”
Section: Plos Onecontrasting
confidence: 90%
“…Given the importance of rapid ART initiation, additional support should be given to new starters so the risk for early default is minimized. Other studies of integrated HIV and maternal‐child healthcare have largely echoed these study findings, highlighting the importance of such integrated care models over the course of pregnancy and breastfeeding to promote adherence and programme retention [60‐64].…”
Section: Resultsmentioning
confidence: 78%
“…Although ART initiation was substantially higher when ART was integrated into ANC, retention in ART care at six and twelve months after ART initiation was similar: 89% and 87% of women who transferred postpartum were retained at six and twelve months, respectively, compared to 80% retention at both six and twelve months among women who transferred to start ART during pregnancy [15]. When comparing transition to ART services at six weeks postpartum to transition after cessation of breastfeeding in South Africa, gaps in care were observed soon after transition in both groups with similar trajectories [27]. By 36 months postpartum, 57% of women transferred at six weeks and 45% of women transferred after weaning had experienced a gap in care.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that reported retention in care after a successful transition observed that once women had transitioned to a new clinic, the majority (>60% across studies) were retained, underscoring that the transition is the vulnerable point [15,24,26,40]. Similarly, a study comparing transition point 3 with transition at six weeks postpartum versus after weaning found similar trajectories in time to loss from care in both groups after transition [27].…”
Section: Discussionmentioning
confidence: 99%